Study guides

Q: 3x squared - x squared

Write your answer...

Submit

Related questions

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)

3x squared

3x2 + x = x*(3x + 1)

3x squared - (3x) squared = 0

5x2 + 3x + 8x2 = 13x2 + 3x = x(13x + 3)

(3x2 - 6x)/3x = 3x(x-2)/3x = x-2, for x<>0

7

(3x + 3y)(x + y) = 3(x + y)2

x^2+2x^2=3x^2

It is: 3x*(x+7)

x(3x - 2)

If that's -18y2, the answer is (3x - 2y)(x + 9y)

3x^2+3x-60=3(x^2+x+20)=3(x+5)(x-4)

It is: x(x+3)

It is: x(x-3) factorized

It is a quadratic equation in X.

X squared - 3x - 10 = 0 (x-5) (x+2) = 0 x - 5 = 0 x + 2 = 0 X= 5 x = -2

-1

13

3x² - 22x - 16 = (3x + 2)(x - 8)

(x^2-2) (x^2+3x+5)= x^2(x^2+3x+5) -2(x^2+3x+5)= x^4 +3x^3 +5x^2 -2x^2 -6x -10= x^4 +3x^3 +3x^2 -6x -10

2x2 x 3x2 = 6 x4 (2x)2 x (3x)2 = 36 x4

3x2+x-2 = (3x-2)(x+1) when factored

(x - 4)(3x - 2)

(x - 8)(3x + 4)

People also asked